Rescue of prepulse inhibition deficit and brain mitochondrial dysfunction by pharmacological stimulation of the central serotonin receptor 7 in a mouse model of CDKL5 Deficiency Disorder. (January 2019) - Vigli, Daniele; Rusconi, Laura; Valenti, Daniela; La Montanara, Paolo; Cosentino, Livia; Lacivita, Enza; Leopoldo, Marcello; Amendola, Elena; Gross, Cornelius; Landsberger, Nicoletta; Laviola, Giovanni; Kilstrup-Nielsen, Charlotte; et al.
Abstract: Mutations in the X-linked cyclin-dependent kinase-like 5 ( CDKL5 ) gene cause CDKL5 Deficiency Disorder (CDD), a rare neurodevelopmental syndrome characterized by severe behavioural and physiological symptoms. No cure is available for CDD. CDKL5 is a kinase that is abundantly expressed in the brain and plays a critical role in neurodevelopmental processes, such as neuronal morphogenesis and plasticity. This study provides the first characterization of the neurobehavioural phenotype of 1 year old Cdkl5 -null mice and demonstrates that stimulation of the serotonin receptor 7 (5-HT7 R) with the agonist molecule LP-211 (0.25 mg/kg once/day for 7 days) partially rescues the abnormal phenotype and brain molecular alterations in Cdkl5- null male mice. In particular, LP-211 treatment completely normalizes the prepulse inhibition defects observed in Cdkl5- null mice and, at a molecular level, restores the abnormal cortical phosphorylation of rpS6, a downstream target of mTOR and S6 kinase, which plays a direct role in regulating protein synthesis. Moreover, we demonstrate for the first time that mitochondria show prominent functional abnormalities in Cdkl5- null mouse brains that can be restored by pharmacological stimulation of brain 5-HT7 R. Highlights: Characterization of behavioural phenotype in fully symptomatic Cdkl5 -null mice. The 5HT7R agonist LP-211 normalizes prepulse inhibition defects in Cdkl5 -null mice. LP-211 treatment rescues brain mitochondrial dysfunction in Cdkl5 -null mice. The abnormal phosphorylation of rpS6 in Cdkl5 -null cortex is restored by LP-211.